2022
DOI: 10.5817/cp2022-4-2
|View full text |Cite
|
Sign up to set email alerts
|

Self-disclosure on social networks: More than a rational decision-making process

Abstract: Although consequences of sharing personal information can be negative and severe (e.g., identity theft), individuals still engage in extensive self-disclosures on social networks. One commonly applied explanatory approach is the privacy calculus. Following this, self-disclosures can be conceptualized as rational choices resulting from a weighing of risks and benefits. However, this view misses the additional impulsive nature of decisions. The current study therefore takes the lens of dual-process theories and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 63 publications
0
13
0
Order By: Relevance
“…Future studies should therefore investigate interactions and interrelations between different features more systematically and also how these are associated with perception processes, neural activations, evaluation processes, and finally the respective decision. Systematic variations of the decision situation and experimentally manipulating different proposed features will help to better understand individuals’ decisions under different circumstances (see also Ostendorf et al, 2022 ). Moreover, by focusing on actual behavior rather than self-disclosure intentions, and by conducting longitudinal investigations by, for instance, applying ambulatory assessment tools, casual relationships can be better understood and protective approaches can be optimized.…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
See 4 more Smart Citations
“…Future studies should therefore investigate interactions and interrelations between different features more systematically and also how these are associated with perception processes, neural activations, evaluation processes, and finally the respective decision. Systematic variations of the decision situation and experimentally manipulating different proposed features will help to better understand individuals’ decisions under different circumstances (see also Ostendorf et al, 2022 ). Moreover, by focusing on actual behavior rather than self-disclosure intentions, and by conducting longitudinal investigations by, for instance, applying ambulatory assessment tools, casual relationships can be better understood and protective approaches can be optimized.…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…Besides, research has shown that warning messages with information on potential negative consequences can support more deliberate self-disclosure decisions, thus likely triggering reflective processes. For instance, for individuals who received a warning message on a fictitious social network that informed about possible short- and long-term negative consequences, the likelihood of creating a post (rather than not creating a post) was lower compared to those who did not receive a warning message ( Ostendorf et al, 2022 ). For those who proceeded creating a post, however, the presentation of this warning message did not reduce the amount of shared information within the post, thus calling for more research.…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
See 3 more Smart Citations